Various factors involved in control, treatment, and investigation of bovine respiratory disease in high risk feedlot cattle - Torres, Siddartha (Kansas State University, 2013)
Bovine Respiratory Disease Complex (BRDC) is the most common and costly disease in feedlot cattle in North America. Annual economic losses are estimated to be US$1 billion due to mortality, reduced performance, and treatment costs. The disease is a multifactorial syndrome caused by a combination of environmental factors, management practices, animal susceptibility, and viral and bacterial pathogens. The objectives of this dissertation were to evaluate two injectable antimicrobials for the treatment and control of BRDC in feedlot cattle, investigation of factors associated with BRDC mortality and morbidity, and to develop control charts based on statistical process control (SPC) principles to monitor cattle mortality rates. Two multi-site prospective studies were conducted to evaluate the comparative efficacy of the administration of gamithromycin and tulathromycin for the treatment and control of BRDC. A total of 2,529 animals were enrolled at two commercial feedlot locations to evaluate the efficacy of the antimicrobials to control BRDC. Morbidity due to BRDC was higher (P = 0.03) among calves receiving gamithromycin compared with those receiving tulathromycin; however, treatments were considered bioequivalent (P < 0.05) for BRDC mortality, case fatality rate and re-treatment rate. Final BW, ADG, DMI and F:G, were similar (P<0.05) between the groups of calves receiving gamithromycin and tulathromycin. For the evaluation of treatment efficacy, a total of 1,049 calves were enrolled in the study. Re-treatment rate was higher among animals treated with gamithromycin compared with those treated with tulathromycin. Treatments were bioequivalent (P < 0.05) for case fatality rate, final BW, and ADG. To evaluate factors associated with BRDC, a retrospective study was conducted to analyze BRDC mortality and morbidity associated with initial body weight, rectal temperature, and castration and dehorning (tipping) at processing. Calves with lighter weights and fever at processing were at greater risk of mortality and morbidity due to BRDC. Also, bulls castrated at processing were at higher risk of developing BRDC. Finally, we developed control charts based on SPC principles to monitor and identify “normal” and special cases of variation of mortality rate. In feedlot cattle, monitoring lots of cattle through SPC principles can be used as a powerful tool for continuous improvement.
Keywords: Bovine respiratory disease; Animal Diseases (0476); Animal Sciences (0475); Veterinary Medicine (0778)